2007
DOI: 10.1158/1078-0432.ccr-07-0640
|View full text |Cite
|
Sign up to set email alerts
|

PrLZ Is Expressed in Normal Prostate Development and in Human Prostate Cancer Progression

Abstract: Purpose: We previously reported the isolation and characterization of PrLZ, a novel prostatespecific and androgen-responsive gene of the tumor protein D52 family at chromosome 8q21.1. PrLZ is the only known gene in this locus with prostate specificity. Expression level of PrLZ was elevated specifically in cancer cells, suggesting its association with malignancy. Experimental Design:To define its biological function in the morphogenesis, development, and functional maturation of the prostate gland and to gain f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 29 publications
4
43
0
Order By: Relevance
“…Androgen-independent, tumorigenic, and bone metastatic C4-2 expressed higher PrLZ levels than that of LNCaP in the LNCaP/C4-2 PCa progression model. Our very recent publication also showed that PrLZ expressed in normal prostate development and in human prostate cancer progression by immunochemistry staining [12]. These data from the above indicated PrLZ has an oncogenic property and contribute to the progression of PCa.…”
Section: Introductionmentioning
confidence: 54%
“…Androgen-independent, tumorigenic, and bone metastatic C4-2 expressed higher PrLZ levels than that of LNCaP in the LNCaP/C4-2 PCa progression model. Our very recent publication also showed that PrLZ expressed in normal prostate development and in human prostate cancer progression by immunochemistry staining [12]. These data from the above indicated PrLZ has an oncogenic property and contribute to the progression of PCa.…”
Section: Introductionmentioning
confidence: 54%
“…74,75 Expression of TPD52 in cancer TPD52 is an overexpressed tumor self-protein actively involved in transformation, leading to increased proliferation and metastasis. TPD52 overexpression has been demonstrated in several human malignancies including breast, [76][77][78] prostate, [79][80][81] and ovarian carcinomas. 82 Expression microarray and other analyses predict TPD52 overexpression in many other cancers including multiple myeloma, 83,84 Burkitt's lymphoma, 85,86 pancreatic cancer, 87 testicular germ cell tumors, [88][89][90] and melanomas, 91,92 as well as multiple other adult and pediatric cancers.…”
Section: 73mentioning
confidence: 99%
“…TPD52 is an oncogene, which is overexpressed in ovarian, breast, and PCas due to gene amplification. 15,18,35 TPD52 gene is located at the chromosome 8q21.1, which is most frequently amplified in PCa. TPD52 expression in different cancer cell types is linked to various cellular functions including proliferation, and its expression is regulated by testosterone in hormone-responsive PCa cells.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] Recent studies have demonstrated that TPD52 promotes metastasis; its expression increases with advancement of cancer and regulates apoptosis of cancer cells. 18,19 There was ample of interest given to TPD52 as an oncogene, due to its multifaceted functions in various cellular mechanisms and multiple carcinomas. 20,21 It is also proved that TPD52 increases lipid metabolism by facilitating de novo synthesis, exogenous uptake, and intracellular lipid storage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation